PENUNDAAN KEHAMILAN DENGAN CARA ‘AZL PERSPEKTIF M. QURAISH SHIHAB - Rohman Wahid, Abdur (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2025)
In the implementation of pregnancy regulation or family planning, one of the methods is through the practice of 'azl. The postponement of pregnancy in the Qur'an and Hadith is not explicitly explained regarding its definitive legal status and falls under contemporary issues. In the matter of 'azl, there are differing opinions among scholars, some permitting it and others prohibiting it. The results of research on the legality of postponing pregnancy through 'azl from the perspective of M. Quraish are as follows: 'Azl is the act of a husband ejaculating his sperm outside the wife's womb to prevent pregnancy. According to M. Quraish Shihab, postponing pregnancy through 'azl is permissible if it is not accompanied by coercion. The legal basis used by Istinbāṭ M. Quraish Shihab includes HR. Muslim no. 3634.